Assessment of the eating disorders and relationship with dental caries, age, gender, and body mass index in a sample of Turkish adolescents aged 9 through 15 - KARGÜL, BETÜL (My University, 2022)
Background and Aims: Eating disorders (ED) are an important public health problem for adolescents due to changing eating attitudes. Using the Eating Attitude Test (EAT-26) with a sample of Turkish adolescents aged 9-15 years, this study evaluated the behavioral risk of ED and its association with dental caries, age, body mass index (BMI), and gender. Subjects and Methods: The EAT-26 scoring system was used, and variables examined included demographic, familial, sociocultural, social, and clinical features. Data were analyzed using SPSS (R) Statistics for Windows, version 20.0. (IBM, New York, NY, USA). Results: A total of 112 adolescents, 46 (41.1%) boys, and 66 (58.9%) girls (mean age 11.46 +/- 1.91 years), were evaluated. EAT-26 mean scores were 16.0 (10.0-21.0) for girls and 14.0 (12.0-23.0) for boys (Mann Whitney U test; P = 0.509). There was no statistically significant difference between the mean BMI scores and the mean EAT-26 scores for girls and boys (Mann Whitney U test) (P = 0.509) (P = 0.636). The mean DMFT decay -missing -filled and total) was higher in EAT-26 > 20 than in EAT-26 < 20, and the difference was statistically significant (Mann Whitney U test; P = 0.008). BMI was not correlated with EAT-26 (Spearman rank correlation test, r =-0.013, P = 0.156), but there was a statistically significant positive correlation between the development of caries and age (Spearman rank correlation test, r = 0.405, P < 0.05). Conclusion: Early diagnosis of ED is crucial because it primarily starts during childhood and adolescence. It is responsible for the dft of the deciduous teeth. BMI is related to decay,missed,filled,total (DMFT), decay, filled, total (dft), and age in adolescents aged 9-15 years. Furthermore, we searched subgroups of EAT-26 for dental caries. Dieting score may be a significant factor for dental caries for ED. However, observing ability is an important factor for dentists because they can inform parents and provide information on preventing ED.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Aile Sağlığı; Temel Bilgi ve Beceriler; Genel Sağlık Meslekleri; Patofizyoloji; Dahiliye; Değerlendirme ve Teşhis; Tıp (çeşitli); Genel Tıp; Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Caries detection; eating behaviors; preventive dentistry; ANOREXIA-NERVOSA; ATTITUDES TEST; BULIMIA-NERVOSA; ORAL-HEALTH; OBESITY; ASSOCIATION; PREVALENCE; OVERWEIGHT; EPIDEMIOLOGY; BEHAVIORS